A Facile Route for the Large Scale Fabrication of Graphene Oxide Papers and Their Mechanical Enhancement by Cross-linking with Glutaraldehyde - Hu, Nantao; Meng, Lei; Gao, Rungang; Wang, Yanyan; Chai, Jing; Yang, Zhi; Kong, EricSiu-Wai; Zhang, Yafei (Nano-Micro Letters, 2011)
A facile route for the large scale production of graphene oxide (GO) papers and their mechanical enhancement has been presented in this work. The novel paper-like GO made from individual GO sheets in aqueous suspension can be achieved in large scale by a simple drop casting method on hydrophobic substrates. Significant enhancement in mechanical stiffness (341%) and fracture strength (234%) of GO paper have been achieved upon modification with a small amount (less than 10 wt%) of glutaraldehyde (GA). The cross-linking reaction takes place between hydroxyl groups on the surface of GO and aldehyde groups of GA, through forming hemiacetal structure, which can result in distinct mechanical enhancement of the GO papers.